Comparative analysis of WC-NiCr, AL₂O₃-NiCr, and CR₃C₂-NiCr metal-ceramic coatings applied by HVOF and detonation spraying methods - Kussainov, A.Y.; Kaliaskarova, M.T.; Abizhanova, I.K.; Molbossynov, Y.S.; Bayatanova, L.B.; Zhunissova, G.Zh. (Recent Contributions to Physics, 2026)
The paper presents a comparative analysis of technologies for forming metal-ceramic coatings of WC-NiCr, Cr₃C₂-NiCr, and Al₂O₃-NiCr systems obtained by high-velocity oxygen fuel (HVOF) and detonation spraying methods. The aim of the study was to determine the influence of the coating technology on the microstructure, physical-mechanical and tribological properties of the coatings. The study included analysis of the morphology of the starting powders and the microstructure of the coatings using scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). Microhardness was determined using the FISCHERSCOPE HM 2000 system, and tribological characteristics were studied using the ball-on-disc method on an Anton Paar TRB³ tribometer in accordance with ASTM G133-95 and ASTM G99 standards. It was found that the spraying method has a significant effect on the structure and performance characteristics of coatings. For carbide systems (Cr₃C₂-NiCr and WC-NiCr), the HVOF method is more effective, providing the formation of a dense, fine-grained structure, increased hardness, and a reduced friction coefficient. For the Al₂O₃-NiCr oxide system, detonation spraying proved to be preferable, providing higher hardness and stable tribological characteristics. The results obtained allow for a reasonable choice of coating formation technology depending on their composition and operating conditions.